Coastal Ecosystem Resilience: Mangrove and Coral Reff Ecosystem Sygnificance for Human and Nature - Muhammad Soimin (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Coastal ecosystem is one the most significant ecosystem on earth supporting numerous natural processes and human life. The two significant ecosystems which play that role are mangroves and coral reefs ecosystems. As earth is cover by water area where coral reefs occur and lands in between where mangroves occur possess a pivotal combination of supportive ecosystem functions including ecological and socio-economic values.However, apart from its’ significances, they are being threatened by antropogenic activities and this is being worsened by cimate changes. Some emerging challanges have to be faced and tackled in order to create a sustainable coastal management and conservation. This has to involve many stakeholders, governments, local people, or non-governmental organizations to work together within beneficial collaborative works. Certain sustainable steps can be promotedwithin the context of management and conservation of coastal ecosystem for mangroves and reefs: 1) decide reefs are wanted and recognize their value; 2) adopt the precautionary principle in making management decisions; 3) reduce reef overexploitation; 4) use science for managing more effectively; 5) do new science to advance management; and 6) recognize and take advantages of synergy among impacts and among management actions.If we do not do these immediate actions, the extinction of mangroves and reefs are likely to happen, then resulting in worse impacts for people.